Knowledge and Experiences of Safety and Health Occupation Risks among Students - Tureková, Ivana; Bagalová, Terézia (International Journal of Engineering Pedagogy (iJEP), 2018)
Occupational safety and health should be the subject of education, as it prepares students for their future occupation, and further adult education, including retraining. Nowadays, as society supports technical education via dual learning, this issue is becoming particularly necessary. Schools ensure students’ safety and health in education, training and other related activities as well as in the provision of school services. In order to secure this task the schools adopt preventive measures based on risk assessment associated with the school activities and environment. When establishing specific measures the school takes into account predominantly the possible threat to students in education of individual subjects, movement within school, and the participation of students in various school-organised events. Subsequently, the educational institution provides continuous education in this area for its students and employees and requires the observance of relevant legal standards by systematic control. It takes into account the age of students, their abilities, and their physical and mental maturity. The aim of this article was to find out how students at different age levels (students of secondary school and elementary schools) understand and observe the principles of safety and health which is a central prerequisite in preparedness for future occupation. In the conclusion part of this paper, we present some solution suggestions; highlight the importance of suitable curricula at schools and educational institutions. Education methods must reflect current, valid and enforceable safety and health regulations at work. It is therefore essential that risk assessment is included in the education process.